Drone technology in architecture, engineering and construction : a strategic guide to unmanned aerial vehicle operation and implementation /: a strategic guide to unmanned aerial vehicle operation and implementation. (2020) - Tal, Daniel, 1971-; Altschuld, John, 1986-
No abstract available